Notas sobre la validez de los pactos prenupciales (y maritales) - Vega Mere, Yuri (2024)
In Peru, fears persist about the reform of family law; after 40 years of the Civil Code (1984), the author persists and incorporates new reasons to agree to its ‘contractualization’ as a reflectionof a society that is less and less willing to marry.We are faced with a regulation that prolongs the marital crisis and is counterproductive for the system itself.The article uses the American experience and the initiatives of the Uniform Law Commission or the American Law Institute to demonstrate the complementarity that can exist between the freedom of the parties to enter into marital or premarital agreements and the subsequent judicial scrutiny. It is emphasized that a modernization of family law does not involve the renunciation of the family law principles.